Climate Change Impact Vulnerability Assessment: The Case of Coastal Communities in Central Zambales, Philippines - SERRANO, Shirly C.; TANGTHAM, Nipon; BUALERT, Surat; JANYASUTHIWONG, Suthee (Journal of Environmental Management and Tourism; Vol 15 No 1 (2024): JEMT, Volume XV, Issue 1(73), Spring 2024DO - 10.14505/jemt.v15.1(73).02, 2024)
The Philippines is one of the countries most affected by climate change. As an archipelago country, coastal areas are at high risk of sea level rise due to climate change. This study investigated the vulnerability of coastal areas to sea level rise in selected municipalities in Zambales province, Philippines. The results showed that the coastal barangay of Iba City has a “moderate” to “high” level of vulnerability, while Botolan City has a “high” to “very high” level of vulnerability. Limited areas of nature reserves, such as mangrove, seagrass, and coral reef ecosystems, are one of the key factors contributing to high vulnerability. Concerted efforts of the local government units and the residents play a vital role to mitigate impacts of climate change including regular mangrove tree planting, coastal clean-up drive, and strict implementation of environmental policies. While there are many tools used in vulnerability assessment, a simpler yet reliable is recommended as an appropriate for barangay levels. With the identified vulnerability of the communities in sea level rise, possible mitigation measures to cope with the fast-changing climate could now be established.